Sub-critical water technology for enhanced extraction of carbohydrates and protein from chlorella vulgaris microalgae - Awaluddin, Saidatul Aliaa (2017)
Algae have many advantages such as fast growth rate, non-arable land requirement for grow and contain substantial amount of biochemical compounds such as lipid, carbohydrate and protein for value added products production. One of the new key alternatives is to extract microalgal biochemical by utilizing subcritical water extraction (SWE). This technique applies hot water under pressure sufficiently retains water in liquid state at temperature below the supercritical values. This study investigates the effectiveness of SWE to extract protein and carbohydrate from microalgae, Chlorella Vulgaris. The study was divided into three parts; (i) investigation of various parameters that affect the biochemical production (protein and carbohydrates), (ii) optimization of SWE and (iii) pre-treatment validation. Four different parameters include temperature (180-374 ˚C), time (1-20min), biomass loading (5-40 wt%) and particle size of biomass (38-250μm) were used to investigate on microalgal SWE. The SWE process was further optimized using central composite design (CCD). It was found that the highest protein and carbohydrate concentration of 31.16 g/100 g and 14.2 g/100gwere obtained at 5 wt.%microalgal biomass with 90 μm particulate size treated at 277°C for 5 min. The TOC yield of 8.01g/100g was obtained at 229ºC for 3min with 10wt.%microalgal biomass at 75μm particle size. Based on the statistical analysis, microalgae loading and extraction temperature have shown the most significant factors that affect the overall extraction of protein whereas extraction temperature were the significant factors for carbohydrate production. TOC yields were only affected by the microalgal loading of the microalgal biomass. This study was further investigated the effect of pre-treatment prior to microalgal SWE. The biomass was irradiated under sonication as the pre-treatment technique with different process parameters. The results concluded that the pre-treatment was not required as the results were comparable with SWE without pre-treatment hence it gives advantages in reducing the extraction costs and avoiding environmental problems (e.g. usage of solvents).